Candidate Drugs Screening for Behcet’s Disease Based on Bioinformatics Analysis and Mouse Experiments - Xia, Qinyun; Lyu, Chujun; Li, Fang; Pang, Binbin; Guo, Xiaoyu; Ren, He; Xing, Yiqiao; Chen, Zhen (Frontiers in Immunology, 2022)
Background: Behcet's disease (BD) is a chronic immune disease that involves multiple systems. As the pathogenesis of BD is not clear, and new treatments are needed, we used bioinformatics to identify potential drugs and validated them in mouse models. Methods: Behcet's disease-related target genes and proteins were screened in the PubMed and UVEOGENE databases. The biological functions and pathways of the target genes were analyzed in detail by GO and KEGG analyses. A protein-protein interaction (PPI) network was constructed by the STRING database, and hub genes were identified by the Cytoscape plug-in CytoHubba. Gene-drug interactions were identified from the DGIdb database. Experimental autoimmune uveitis (EAU) mice were used as an animal model for drug validation. Results: A total of 249 target genes and proteins with significant differences in Behcet's disease were screened, and the results of functional enrichment analysis suggested that these genes and proteins were more located on the cell membrane, involved in regulating the production of cytokines and affecting the activity of cytokines. They mainly regulated “Cytokine- Cytokine receptor interaction”, “Inflammatory disease (IBD)” and “IL-17 signaling Pathway”. In addition, 10 hub genes were obtained through PPI network construction and CytoHubba analysis, among which the top 3 hub genes were closely related to BD. The DGIdb analysis enriched seven drugs acting together on the top 3 hub genes, four of which were confirmed for the treatment of Behcet's disease or its complications. There is no evidence in the research to support the results in Omeprazole, Rabeprazole, and Celastrol. However, animal experiments showed that Rabeprazole and Celastrol reduced anterior chamber inflammation and retinal inflammation in EAU mice. Conclusions: The functional analysis of genes and proteins related to BD, identification of hub genes, and validation of potential drugs provide new insights into the disease mechanism and potential for the treatment of BD.